The significance of the different names applied by historians to the events of 1857 - Syed Hussain Shaheed Soherwordi (Journal of Political Studies, 2013)
The nature of the uprising of 1857 has aroused from the very beginning, serious controversy. The official British explanation was that the Bengal Native Army had alone mutinied, and any civil disturbances that occurred after, were natural by-products of the collapse of law and order. A British official, William Muir argued that, ‘the character of the affair is that of a military mutiny-a struggle between the Government and its Soldiers, not between the Government and the People’. However, this view has been contested largely by writers and historians who argue that the rebellion of 1857 was not solely a military act but involved individuals from various backgrounds.